PERANAN MODAL USAHA DAN MODAL MANUSIA DALAM MENINGKATKAN KINERJA UMKM DI KABUPATEN BOALEMO - Alfin Akuba; Hasmirati Hasmirati (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The role of business capital and human capital in improving the performance of MSMEs in Boalemo Regency. This study aims to determine and analyze how big the influence of business capital and human capital on the performance of Taylor's MSMEs in Boalemo Regency. Research is quantitative research. The method of analysis using multiple linear regression. The population of this research is the Taylor MSMEs in Boalemo District, especially in Tilamuta District as many as 43 MSMEs. The samples in this study were 43 Taylor SMEs in Boalemo District, Tilamuta District. Based on the results of data analysis that has been carried out, simultaneously Business Capital and Human Capital have a significant effect on Taylor's MSME Performance in Boalemo Regency. Partially, Business Capital has a significant effect on Taylor's MSME Performance in Boalemo Regency. And Human Capital has a significant effect on Taylor's MSME Performance in Boalemo District Peranan modal usaha dan modal manusia dalam meningkatkan kinerja umkm di kabupaten boalemo. Penelitian ini bertujuan untuk mengetahui dan menganalisis seberapa besar Pengaruh Modal Usaha Dan Human Capital Terhadap Kinerja UMKM Taylor Di Kabupaten Boalemo. Penelitian adalah penelitian kuantitatif. Metode analisis menggunakan regresi linier berganda. Populasi penelitian ini adalah UMKM Taylor di Kabupaten Boalemo khususnya di Kecamatan Tilamuta sebanyak 43 UMKM. Adapun Sampel dalam penelitian ini sebanyak 43 UMKM Taylor di Kabupaten Boalemo Kecamatan Tilamuta. Berdasarkan hasil analisis data yang telah dilakukan, secara simultan Modal Usaha dan Human Capital, berpengaruh signifikan terhadap Kinerja UMKM Taylor di Kabupaten Boalemo. secara parsial Modal Usaha berpengaruh signifikan terhadap Kinerja UMKM Taylor di Kabupaten Boalemo. Dan Human Capital berpengaruh signifikan terhadap Kinerja UMKM Taylor di Kabupaten Boalemo.